Penilaian Kapabilitas Tata Kelola Keamanan Informasi Menggunakan Cobit5 Pada PT.Denya - Ikhwan, Ali; Ardiyansyah, Agung; Rayhannur, Muhammad Jaffar; Hidayat, Riyan (CV. Information Technology Training Center - Indonesia (ITTC), 2023)
This research assesses the copability of asset and information security governance using the COBIT5 framewort. The study aims to evaluate the current state of security goverenance in an organization and identify areas of improvement using the COBIT5 framework. The research will analyze the processes and controls in place for managing and protecting information and assets, and assess their aligmnment with the COBIT5 giudelines. The result of the study will procide valuable insights for ornganizations looking to improve their security governance and compliance with industry standards.